Revision of the genus Daldinia in the KRAM herbarium collection: Daldinia childiae, D. loculata and D. loculatoides, three new species for Poland - Chlebicki, Andrzej (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2022)
The article presents the results of the revision of Daldinia (Ascomycota) specimens preserved in KRAM F (Kraków, Poland). The following species were identified: Daldinia childiae, D. decipiens, D. loculata, D. loculatoides, D. petriniae and D. vernicosa. Three of them were not reported from Poland so far: D. childiae, D. loculata, D. loculatoides. Aditionaly to Polish specimens, also some collections from outside Poland are kept in KRAM F: one specimen of D. concentrica from Bulgaria, D. lloydii from Ukraine and D. eschscholtzii from Cameroon.